Profil Terapi Penggunaan Obat BPH (Benign Prostatic Hyperplasia) Tamsulosin dengan Dutasteride pada Pasien Pembesaran Prostat Jinak - Siska Purnama Asih; Yanti, Silfera Indra; Iin Ruliana Rohenti (FARMASIS: Jurnal Sains Farmasi, 2023)
Background: Benign Prostatic Hyperplasia (BPH) is a term for hyperplasia and hyperplasia. stromal cells prostate gland epithelium. Basically, BPH grows in men who are old and have testes that still produce testosterone. Previous studies suggest that the combination of tamsulosin and dutasteride provides a better therapeutic effect for BPH, significantly reducing the risk of developing BPH-related symptoms. Objectives: The purpose of this study was to identify the socio demographics of BPH patients including age and occupation, identify the type of BPH drug therapy and the effectiveness of Tamsulosin therapy and the combination of tamsulosin with dutasteride based on the duration of drug therapy in Outpatient BPH patients Method: the research was descriptive design with a cross-sectional by looking at the description of the type of BPH drug therapy. Results: From the results of the study, it was found that a sample of 136 BPH patients, BPH patients were more common in the age group 60-74 (75 persen), the most occupational status worked as independent workers (53.7 persen), the most type of therapy was combination therapy with tamsulosin and dutasteride (62.5 persen), and duration of combination therapy (tamsulosin with dutasteride) more than 1 year (39 persen). Conclusion: The period of combination therapy is per the effectiveness of the duration of BPH drug therapy.